2015
DOI: 10.1371/journal.pone.0126065
|View full text |Cite
|
Sign up to set email alerts
|

Use of Xpert MTB/RIF in Decentralized Public Health Settings and Its Effect on Pulmonary TB and DR-TB Case Finding in India

Abstract: BackgroundXpert MTB/RIF, the first automated molecular test for tuberculosis, is transforming the diagnostic landscape in high-burden settings. This study assessed the impact of up-front Xpert MTB/RIF testing on detection of pulmonary tuberculosis (PTB) and rifampicin-resistant PTB (DR-TB) cases in India.MethodsThis demonstration study was implemented in 18 sub-district level TB programme units (TUs) in India in diverse geographic and demographic settings covering a population of 8.8 million. A baseline phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 6 publications
7
83
0
Order By: Relevance
“…The patient population screened, which comprised presumptive drug-resistant cases and patients with human immunodeficiency virus with TB symptoms, contributed to the high RR-TB detection rate. The main impetus was the timely detection of multidrug-resistant TB, [16][17][18][19] as RMP resistance is a surrogate for isoniazid resistance. 20,21 The key lesson learnt from the Xpert roll-out was that access to diagnosis is not the only indicator for measuring successful implementation; the rate of unsuccessful tests (which add no value to treatment) is also an important indicator of the effectiveness of Xpert implementation over time.…”
Section: Public Health Actionmentioning
confidence: 99%
“…The patient population screened, which comprised presumptive drug-resistant cases and patients with human immunodeficiency virus with TB symptoms, contributed to the high RR-TB detection rate. The main impetus was the timely detection of multidrug-resistant TB, [16][17][18][19] as RMP resistance is a surrogate for isoniazid resistance. 20,21 The key lesson learnt from the Xpert roll-out was that access to diagnosis is not the only indicator for measuring successful implementation; the rate of unsuccessful tests (which add no value to treatment) is also an important indicator of the effectiveness of Xpert implementation over time.…”
Section: Public Health Actionmentioning
confidence: 99%
“…These data would enable us to evaluate the incremental number of transmissions that a novel test might be able to avert, relative to the existing standard of care. A series of recent high-quality studies suggests that, when patients present with symptoms that are highly suggestive of TB in upper-middle income settings (for example, South Africa and Brazil), the probability of empirical diagnosis is reasonably high [8][9][10][11] -but that a large number of people may be presenting to care with a cough without TB ever being considered 8 . Such studies are crucial to understand the likely diagnostic gaps for TB, but unfortunately, very few such analyses have been performed in settings with fewer resources (for example, most of sub-Saharan Africa 73,74 and Southeast Asia) where empirical diagnosis rates (and the capacity to implement novel diagnostic tests) may be much lower.…”
Section: S65mentioning
confidence: 99%
“…Nevertheless, the link between improved diagnostic sensitivity and better TB detection remains uncertain. Studies [8][9][10][11] in different settings have found little or no change in the number of pulmonary TB diagnoses or deaths when comparing sputum smear microscopy and Xpert MTB/RIF, a more sensitive molecular test 12 . This result may reflect high levels of empirical treatment among people who test negative [13][14][15] .…”
mentioning
confidence: 99%
“…4,5 For an economic analysis of the potential scale-up of Xpert testing in India, unit cost estimates of Xpert, sputum smear microscopy (SSM), as well as of other commonly used tests to diagnose drug-resistant TB in India, were required. Earlier TB diagnostic costing studies in India were from limited settings and conducted during the early stages of Xpert demonstration studies.…”
mentioning
confidence: 99%